Even though you may feel useless... Story about an experience - Raquel Asunción Díaz Alonso; David Palacios Martínez (Universidad de Alicante, 2014)
Work in the health field can be very demanding at the affective level. The emotional component in the personal relationship affects all those involved: patients, families and professionals. It can lead us to feel upset, as in this story, when we believe that our actions have proved futile. On numerous occasions we do not come to know our real impact on the lives of patients. All health professionals have some experience that moves us. This is mine.